Muslim migrants and hybrid placemaking of mosques in Culiat, Quezon City - Ruiz, Act (2018)
Access online through this link: https://journals.upd.edu.ph/index.php/kasarinlan/article/view/7068/6153
Keywords: Mosques; Muslims; Immigrants